Sistem Rekomendasi Tempat Parkir di Kota Lama Semarang Menggunakan Collaborative Filtering - Ahmad Samsul Muarif; Edy Winarno (Universitas Batanghari Jambi, 2022)
Utilization of information and communication technology has become an inseparable part of people's lives today. In the last few years, there have been many studies that have used information technology to solve the problems of everyday life in society. Utilizes Collaborative Filtering and Location Based Filtering methods to build a tourism recommendation system in the special area of Yogyakarta. Based on previous research, the researcher will build a parking recommendation system in the old city of Semarang using the Collaborative Filtering method. Collaborative filtering has two processes, namely the similarity calculation process and the prediction calculation. A similar calculation process is carried out to find the value between parking lots which will continue the prediction calculation process. While the estimation process is carried out to find predictions of parking spaces for visitors. The calculation process that has been carried out on Andi users gets a recommendation on parking lot I2 with the highest score of 0.565, while the lowest score is obtained by parking lot I5 with a score of -0.696.